Pathology of tropical appendicitis. Issue 11 (November 1989) - Gupta, S C; Gupta, A K; Keswani, N K; Singh, P A; Tripathi, A K; Krishna, V
Abstract : Over the past 25 years, 2921 appendicectomies were performed at this hospital. All were subjected to routine histopathological examination. In 95% of cases, histopathological examination did not add any further information but in 153 (5%) cases, clinically important pathological findings were detected for the first time. Seventy (2.3%) specimens showed typical evidence of tuberculosis. Parasitic infestation was detected in 75 (2.5%), including enterobiasis (1.4%), amoebiasis (0.5%), ascariasis (0.5%), ascariasis with trichuriasis (0.05%), and taeniasis (0.05%). Other lesions found were mucocele (0.1%) and carcinoid tumour (0.1%). It is concluded that routine histopathological examination of all appendicectomy specimens should be performed to avoid missing any clinically important and treatable condition.